2020
DOI: 10.1371/journal.pone.0240149
|View full text |Cite
|
Sign up to set email alerts
|

In-silico drug repurposing study predicts the combination of pirfenidone and melatonin as a promising candidate therapy to reduce SARS-CoV-2 infection progression and respiratory distress caused by cytokine storm

Abstract: From January 2020, COVID-19 is spreading around the world producing serious respiratory symptoms in infected patients that in some cases can be complicated by the severe acute respiratory syndrome, sepsis and septic shock, multiorgan failure, including acute kidney injury and cardiac injury. Cost and time efficient approaches to reduce the burthen of the disease are needed. To find potential COVID-19 treatments among the whole arsenal of existing drugs, we combined system biology and artificial intelligence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 98 publications
1
67
0
Order By: Relevance
“…The reason behind suggesting Pirfenidone is not simply the similarity of COVID-19 ARDS/Fibrosis and IPF; but the pathogenesis of COVID-19 disease; it's receptor, and the mechanism of action of Pirfenidone. In line with our hypothesis, a recent in-silico drug repurposing study suggested promising modeling results for the combination of Pirfenidone and melatonin as a potential treatment to diminish SARS-CoV-2 infection progression and respiratory distress due to cytokine storm ( 6 ). Nevertheless, at the end of the day, only clinical trials are going to determine if this hypothetical treatment would work.…”
Section: Discussionsupporting
confidence: 78%
“…The reason behind suggesting Pirfenidone is not simply the similarity of COVID-19 ARDS/Fibrosis and IPF; but the pathogenesis of COVID-19 disease; it's receptor, and the mechanism of action of Pirfenidone. In line with our hypothesis, a recent in-silico drug repurposing study suggested promising modeling results for the combination of Pirfenidone and melatonin as a potential treatment to diminish SARS-CoV-2 infection progression and respiratory distress due to cytokine storm ( 6 ). Nevertheless, at the end of the day, only clinical trials are going to determine if this hypothetical treatment would work.…”
Section: Discussionsupporting
confidence: 78%
“…There appears to be no standard approach to treating cytokine release syndromes that currently addresses all three, and the vast majority address none, focusing instead on antagonizing cytokine functions. However, melatonin (N-acetyl-5-methoxy tryptamine) has recently emerged as an effective therapy for severe COVID-19 [ 246 , 247 , 248 , 249 , 250 , 251 ]. While melatonin is often thought of being mainly a sleep regulator, it also has widespread effects on the innate immunity—in particular, antagonizing TLR2, TLR4, TLR9, NLRP3 and, possibly, NOD2 [ 59 , 252 , 253 , 254 , 255 ].…”
Section: Discussionmentioning
confidence: 99%
“…Artigas et al (Artigas et al 2020) utilized a systems biology and AI-based approach, the Therapeutic Performance Mapping System (TPMS) technology (Jorba et al 2020) to repurpose drugs and drug combinations for COVID-19. TPMS method employs an ANN to measure the potential relationship between the nodes of a network (i.e.…”
Section: Ai/ml-based Methods In Covid-19 Drug Repurposingmentioning
confidence: 99%